An efficient multi-scale model for needle-punched Cf/SiCm composite materials with experimental validation. (15th July 2021) - Lim, Hyoung Jun; Choi, Hoil; Lee, Min Jung; Yun, Gun Jin
Abstract: In this paper, we present a novel efficient multi-scale modeling methodology for three-dimensional (3D) needle-punched (NP) carbon/silicon carbide (NP Cf /SiCm ) with a complex microstructure. Variations of the material properties induced by the needle-punching process and complex geometrical features could pose challenges when estimating the material's behavior. A 3D microscopic high fidelity FE model is developed based on micro-CT images considering these composites' features. Novel and viable image processing techniques of micro-CT images are presented to generate the high fidelity model. The 3D high fidelity FE model is validated with the experimental test at room and high temperatures. A novel subcell modeling technique is developed for the 3D NP Cf /SiCm referring to the high fidelity FE model to expand to the macro-scale structural problem. The proposed models compare excellently with experimental results for mechanical behavior of tensile, shear, and bending under static loading conditions.